Structure and Properties of Lantern‐Shaped Hexapalladium Complexes with Germylene and Thiolate Ligands [Pd6(µ‐GePh2)2(µ‐SC6H4‐p‐X)2(CN‐C6H3Me2‐2, 6)8] (X = NO2, Cl, H, CH3). Issue 23 (3rd June 2020) - Koizumi, Take‐aki; Tsuchido, Yoshitaka; Ide, Tomohito; Osakada, Kohtaro
Abstract : Reaction of diaryl disulfides, ArSSAr (Ar = C6 H4 ‐ p ‐Cl, Ph, C6 H4 ‐ p ‐CH3 ) with a hexapalladium complex with bridging germylene ligands, [Pd6 (µ‐GePh2 )2 (CN‐C6 H3 Me2 ‐2, 6)8 (µ‐CN‐C6 H3 Me2 ‐2, 6)2 ] (1 ) afforded arylthiolate‐bridged complexes, [Pd6 (µ‐GePh2 )2 (µ‐SAr)2 (CN‐C6 H3 Me2 ‐2, 6)8 ] (Ar = C6 H4 ‐ p ‐Cl, Ph, C6 H4 ‐ p ‐CH3 ) (3–5 ). The Pd (0) 4 Pd (I) 2 complexes as well as analogous complex with 4‐nitrophenylthiolate ligands [Pd6 (µ‐GePh2 )2 (µ‐SC6 H4 ‐ p ‐NO2 )2 (CN‐C6 H3 Me2 ‐2, 6)8 ] (2 ) have a hexagonal bipyramidal structure which contains two bridging thiolate ligands at basal coordination sites. Electrochemical measurement of 2 –5 showed one reversible redox wave at E 1/2 = –0.51 (2 ), –0.61 (3 ), –0.66 (4 ) and –0.70 (5 ) V (vs. Fc + /Fc) in the oxidation region, and irreversible reduction peak at E pc = –2.04 (2 ), –2.29 (3 ), and –2.38 (4 ) V (vs. Fc + /Fc) in the reduction region. Both oxidation and reduction potentials are correlated well with Hammett substitution constant σ p of the aryl group of the thiolate ligands. Abstract : Reaction of ArSSAr with diphenylgermylene‐bridged lantern‐shape hexapalladium(0) complex afforded arylthiolate‐bridged complexes, [Pd6 (µ‐GePh2 )2 (µ‐SAr)2 (CN‐C6 H3 Me2 ‐2, 6)8 ] (Ar = C6 H4 ‐ p ‐Cl, Ph, C6 H4 ‐ p ‐CH3 ). The complexes have a [Pd (0) 4 Pd (I) 2 ] core, and hexagonal bipyramidal structure in which two bridging isocyanide ligands of the Pd (0) 6 complex are replaced by the thiolate ligands. The oxidation and reduction potentials of the complexes are correlated with σ p of the aryl group of the thiolate ligands.